Cost of foraging in the subterranean rodent Ctenomys talarum: effect of soil hardness - Luna, Facundo (2006)
Subterranean burrows provide inhabitants with shelter, a relatively stable thermal environment, and potentially access to food resources. However, one cost of living in such burrows is the energetically expensive mode of locomotion. Soil hardness and the physiological capabilities of animals are likely important factors that affect the cost of burrow construction, and hence, distribution of burrows. We assessed the effect of soil hardness on the cost of digging by captive individual Ctenomys talarum Thomas, 1898 in soft soils. Digging metabolic rate (DMR) was higher in harder soil than in softer soil (408.30 ± 51.35 mL O2·h–1 vs. 267.59 ± 20.97 mL O2·h–1, respectively). In C. talarum, a higher soil hardness augments DMR by increasing, in terms of the cost of burrowing model, the costs of shearing and of pushing the removed soil. Additionally, these costs differ between C. talarum and other subterranean species (e.g., Thomomys bottae (Eydoux and Gervais, 1836)), depending on soil hardness and digging mode. Thus, the relationship between digging cost and soil hardness appears to be one of the most important factors that affect burrowing efficiency in subterranean rodents.